Assistance for Micro Businesses of Canang Sari Traders in Penatih Dangin Puri Village, East Denpasar - Nyoman Dwika Ayu Amrita; I Wayan Arya Sugiarta; Tri Hayatining Pamungkas; Anak Agung Gede Agung Indra Prathama (Community Service Journal (CSJ), 2024)
Microenterprises are businesses run by people categorized as poor or near poor. They are family-owned, using local resources and simple technology. Micro-enterprises include unbanked people, a group that is difficult to get access to banking even though this group has the potential to develop business. Canang Sari is the simplest form of offerings in the form of janur made rectangular decorated with various types of flowers that are offered as an effort to get closer to God in prayer. Based on observations, there is a group of canang traders called the Canang Sari Wangi group located in Banjar Laplap Putih, Penatih Dangin Puri Village, East Denpasar who really need help to overcome the problems they face. This Canang Sari Wangi trader group has 5 members who have been established since 2020. The problems faced by this group of Canang Sari Wangi traders are difficult to get access to banking, lack of knowledge for business development due to fluctuations in demand, very fierce competition, high operational costs, lack of understanding of creative marketing and the absence of careful and thorough administration of financial reports. The approach taken is to further coordinate with members of the Canang Sari Wangi Group so as to obtain the main needs for increasing productivity, namely by providing assistance to facilitate access to banking, entrepreneurship assistance, improve creative marketing skills and make business bookkeeping. The output target to be achieved is an increase in the ability of partners to access banking, through creative marketing partners are able to increase group income by 30% and all members of the Canang Sari Wangi group are able to make simple group bookkeeping. The method of implementing this activity is preceded by collecting information from partner conditions, designing activities to be carried out, followed by program socialization, conducting training, mentoring and evaluation.